Evaluating Filtration and Thermal Stability of Water-Based Mud Using Green Synthesized Zinc Oxide Nanoparticles - Al-Ogaili, Fatimah H. A.; Almahdawi, Faleh H. M.; Ali , Jagar A. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Nanoparticles (NPs) have unique capabilities that make them an eye-opener opportunity for the upstream oil industry. Their nano-size allows them to flow within reservoir rocks without the fear of retention between micro-sized pores. Incorporating NPs with drilling and completion fluids has proved to be an effective additive that improves various properties such as mud rheology, filtration, thermal conductivity, and wellbore stability. However, the biodegradability of drilling fluid chemicals is becoming a global issue as the discharged wetted cuttings raise toxicity concerns and environmental hazards. Therefore, it is urged to utilize chemicals that tend to break down and susceptible to biodegradation. This research presents the practical application of bio-based Zinc Oxide nanoparticles (ZnO NPs) prepared chemically from celery leaf plant extract as green additive in water-based mud drilling fluid (WBM). The study aimed to evaluate the filtration and thermal stability of WBM using green-synthesized ZnO NPs. The results showed that the ZnO NPs have minimal effect of mud density, but significant improvement in mud thermal stability and filtration properties were attained with concentrations lower than 1g. The fluid loss rate was reduced by 33% with 0.45g of ZnO nanoparticles, and the thinnest mud cake was obtained as well. In terms of thermal stability, the bio-based ZnO NPs greatly enhanced the rheological properties of WBM at elevated temperatures. The rate of increment in plastic viscosity (PV) or decrement in yield point (YP) and gel strength occurred in a controllable manner compared to the rheological properties of base mud at high temperatures reaching 90°C. This study provides insight into the effect of green-synthesized ZnO nanoparticles on the performance of water-based mud and highlights their potential as an effective and environmentally friendly additive for the oil and gas industry.